Recent advances in the effective removal of hazardous pollutants from wastewater by using nanomaterials—A review - Chahar, Mamta; Khaturia, Sarita; Singh, Har Lal; Solanki, Vijendra Singh; Agarwal, Neha; Sahoo, Dipak Kumar; Yadav, Virendra Kumar; Patel, Ashish (Frontiers in Environmental Science, 2023)
Environmental nanotechnology has developed rapidly over the past few decades due to the fast advancement of nanotechnology and nanomaterials (NMs). Due to their nanoscale size, NMs are receiving immense attention in research and development worldwide. Their nano size has led to better catalysis, high reactivity, and high adsorption capacity. In wastewater treatment, nanotechnology has significant potential to improve the performance and efficiency of water decontamination; more effectively, it provides a sustainable way to keep water supplies safe. Numerous studies have found that removing harmful components from wastewater by employing nanoparticles in conjunction with various treatment methods is effective. The purpose of the current investigation is to conduct a review of the envisioned applications of various NMs in the treatment of wastewater. These NMs include carbonaceous NMs, metal-containing nanoparticles, and nanocomposites, all of which will be reviewed and highlighted in depth.